Association of increased arterial stiffness with diastolic dysfunction in ischemic stroke patients: the Norwegian Stroke in the Young Study. Issue 3 (March 2020) - Einarsen, Eigir; Gerdts, Eva; Waje-Andreassen, Ulrike; Naess, Halvor; Fromm, Annette; Saeed, Sahrai
Abstract : Background: Young and middle-aged ischemic stroke survivors have a high prevalence of hypertension, increased arterial stiffness and abnormal left ventricular (LV) geometry, which all are associated with the presence of LV diastolic dysfunction. However, the prevalence and covariates of diastolic dysfunction in these patients have not been reported. Objectives: To explore diastolic dysfunction in ischemic stroke patients aged 15–60 years included in the Norwegian Stroke in the Young Study. Methods: Data from 260 patients with acute ischemic stroke was analyzed. Diastolic dysfunction was assessed by combining transmitral peak early flow ( E ), early diastolic mitral annular velocity ( e ′), E / e ′ ratio, left atrial volume index and peak tricuspid regurgitant jet velocity, following current European guidelines. Carotid–femoral pulse wave velocity at least 10 m/s by aplanation tonometry was defined as increased arterial stiffness. Results: Prevalent diastolic dysfunction was found in 20% of patients (13% with diastolic dysfunction grade 1 and 7% with diastolic dysfunction grades 2–3). Patients with diastolic dysfunction were older and more likely to have hypertension, overweight, increased arterial stiffness, higher LV mass and less percentage nightly reduction in mean blood pressure (BP) (all P < 0.001). In a multivariable logistic regression analysis, diastolic dysfunction was associated with increased arterial stiffness [odds ratio 2.86 (95% confidence interval 1.05–7.79), P < 0.05] independent of age more than 45 years, overweight, hypertension, night-time BP reduction and LV mass. Conclusion: Among young and middle-aged ischemic stroke survivors, diastolic dysfunction was found in 20%. The presence of diastolic dysfunction was associated with increased arterial stiffness independent of higher age, overweight, hypertension, night-time BP reduction and LV mass.